2019
DOI: 10.1007/s00330-019-06054-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MR T1 and T2 mapping parameters to characterize myocardial and skeletal muscle involvement in systemic idiopathic inflammatory myopathy (IIM)

Abstract: Objectives To compare the performance of magnetic resonance (MR) relaxometry parameters to discriminate myocardial and skeletal muscle inflammation in idiopathic inflammatory myopathy (IIM) patients from healthy controls. Materials and methods For this retrospective case-control study, 20 consecutive IIM patients (54 ± 18 years, 11 females) with cardiac involvement (troponin level > 50 ng/l) and 20 healthy controls (47 ± 12 years, 9 females) were included. All patients without cardiac MR imaging < 2 weeks prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…The uncertain conclusions in previous studies may be attributable to differences in patient selection, approaches used to evaluate cardiac abnormalities, different follow-up intervals, and the insufficient sample sizes. In the present study, we found that newly diagnosed IIM patients had significantly elevated T1, T2, and ECV values on both myocardium and skeletal muscles, which are consistent with the findings of previous studies [10,12]. In addition, we also demonstrated for the first time that multiparametric CMR can detect dynamic changes in both myocardial and skeletal tissue characteristics after effective treatment.…”
Section: Abbreviationssupporting
confidence: 92%
See 3 more Smart Citations
“…The uncertain conclusions in previous studies may be attributable to differences in patient selection, approaches used to evaluate cardiac abnormalities, different follow-up intervals, and the insufficient sample sizes. In the present study, we found that newly diagnosed IIM patients had significantly elevated T1, T2, and ECV values on both myocardium and skeletal muscles, which are consistent with the findings of previous studies [10,12]. In addition, we also demonstrated for the first time that multiparametric CMR can detect dynamic changes in both myocardial and skeletal tissue characteristics after effective treatment.…”
Section: Abbreviationssupporting
confidence: 92%
“…In the present study, newly diagnosed IIM patients showed significantly elevated T1, T2, and ECV values in comparison with normal controls, and these findings are consistent with recent CMR studies of IIM patients [10,12]. We also found that the myocardial native T1, T2 and ECV values were significantly correlated with the NT-proBNP level, which may suggest that.…”
Section: Myocardial and Skeletal Muscles Involvement In Iimsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the highly variable intra-and inter-individual ranges of T2 values are a major drawback of and potential diagnostic pitfall for the clinical implementation of T2 values [11]. This impedes the ability to differentiate between healthy and injured myocardium, because pathologic T2 value differences can be relatively low (~10-20 ms) compared to this general variance [12][13][14]. Complex biological variations in the myocardium may serve as one explanation for these variabilities, but additional technical factors influence T2 values [15,16].…”
Section: Introductionmentioning
confidence: 99%